Photochromism in Isotopically Labeled Oxygen‐Containing Yttrium−Hydride and Deuteride Thin‐Film Systems. Issue 4 (26th December 2021) - Moro, Marcos V.; Aðalsteinsson, Sigurbjörn M.; Moldarev, Dmitrii; Wolff, Max; Primetzhofer, Daniel
Abstract : Photochromic mono‐ and bilayered thin films of oxygen‐containing isotope‐labeled yttrium−hydride (i.e., protium and deuterium) are synthesized via reactive Ar sputtering. Selected samples are encapsulated with transparent diffusion barriers. Combining depth‐resolved nondestructive ion beam‐based techniques for composition and optical spectrophotometry, material mobility in the samples during illumination and over time is investigated. The results reveal that deuteride thin films exhibit a strong photochromic response equivalent to hydrogenated systems. No evidence of long‐distance light‐induced hydrogen mobility or thermal diffusion is found. The findings thus show that photochromism is not connected to long‐distance material transport. The observations for encapsulated samples also exclude direct material exchange with the environment and any environmental influence on material mobility. Abstract : Herein, the presence of photochromism in oxygen containing yttriumhydride irrespective of the hydrogen isotope (protium or deuterium) employed during synthesis is demonstrated. Using isotope‐labeled bilayers no further evidence of long‐distance light‐induced hydrogen mobility or thermal diffusion is found. This result shows that photochromism in this system is not connected to long‐distance material transport.